OpenSHMEM and Related Technologies. Experiences, Implementations, and Technologies Second Workshop, OpenSHMEM 2015, Annapolis, MD, USA, August 4-6, 2015. Revised Selected Papers - Gorentla Venkata, Manjunath; Shamis, Pavel; Imam, Neena; Lopez, M. Graham (Programming and Software Engineering, 2015)
This book constitutes the proceedings of the Second OpenSHMEM Workshop, held in Annapolis, MD, USA, in August 2015. The 12 technical papers and one short position papers presented in this book were carefully reviewed and selected from 17 submissions. The topics of the workshop included extensions to the OpenSHMEM API, implementation of the API for current and emerging architectures, tools to debug and profile OpenSHMEM programs, experience porting applications to the OpenSHMEM programming model, and changes to the OpenSHMEM specification to address the needs of programming exascale systems.